Das Handbuch der klassischen Altertumswissenschaft: Enzyklopädisches Wissen im Zeitalter des Historismus - Rebenich, Stefan (Hyperboreus, 2016)
The Handbuch der Altertumswissenschaft (Handbook for the Study of the Ancient World), published by C. H. Beck, both reﬂected and inﬂuenced the disciplinary formation of Altertumswissenschaft in the era of historicism. The handbook offered specialist knowledge for use in universities and schools, and served to disseminate academic knowledge. The way in which the handbook presented, structured, and standardized the vast quantity of knowledge it contained changed the very nature of that knowledge. Its success was based not least on the fact that it transformed the knowledge it transmitted, and thereby helped to modernize the discipline of Altertumswissenschaft itself.